Deep UV resonance Raman spectroscopic study of CnF2n+2 molecules: the excitation of C–C σ bond. (27th October 2012) - Jin, Shaoqing; Guo, Meiling; Fan, Fengtao; Yang, Jingxiu; Zhang, Ying; Huang, Baokun; Feng, Zhaochi; Li, Can
<x xml:space="preserve">Abstract</x> The σ–σ* transition of C–C bond in CnF2n+2 molecules was studied by deep UV resonance Raman spectroscopy. With the C–C σ bond selectively excited by the deep UV laser at 177.3 nm, the resonance Raman spectra of CnF2n+2 molecules were obtained on our home‐assembled deep UV Raman spectrograph. The Raman bands at 1299, 1380 and 2586 cm−1 due to the C–C skeletal stretching modes are evidently enhanced owing to the resonance Raman effect. Based on the resonance Raman spectra and theoretical calculation results, it is proposed that the electronic geometry of CnF2n+2 molecules at the σσ* excited state is displaced along the directions perpendicular and parallel to the C–C skeleton, and the excited C–C bond is not dissociative due to the delocalization of the excited electron in σ* orbital. Copyright © 2012 John Wiley & Sons, Ltd.